Book Review: Delivery as Dispossession: Land Occupation and Eviction in the Postapartheid City. Zachary Levenson, 2022. - Katherine Wiley (Radical Housing Journal, 2024)
Drawing on fieldwork over the course of a decade in two encampments in Cape Town, South Africa, Matthew Levenson’s book uses a Gramscian framework to analyze the dynamics between the state and the organizational formations of encampments. His relational perspective on eviction considers the main factors influencing the likelihood of state-enforced evictions and underlines the effect of different organizing tactics, constructing land occupations as alternative housing versus social movements. In challenging and expanding our understandings of the politics of eviction, the book provides insights for housing movements globally.